MANAJEMEN STRATEGIK SUMBER DAYA MANUSIA DALAM PENDIDIKAN : JALAN MENUJU PENINGKATAN MUTU SEKOLAH - Rio Triyono; Moh. Roqib; Muh. Hanif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research begins with an awareness of strategic management, which presents various beneficial and successful approaches to enhancing the quality and standards of performance in for-profit institutions by demonstrating competitive advantages. Therefore, it is hoped that this writing can serve as a subject of study for educational institutions in the process of improving educational quality by implementing strategic management concepts within their organizations. The method employed in this research is qualitative, utilizing a library research approach. The data serving as instruments in this study consist of various information gathered from books, journals, and articles from previous research, employing documentation as the data collection technique and content analysis for data analysis. The findings of this research indicate that the role of educational institution leaders is crucial in formulating strategies for improving the quality and standards of educational institutions. The implementation of strategic human resource management is highly necessary to enhance student achievement through the teaching and strategies employed by educators in their learning practices. Strategic evaluation is conducted by educational institution stakeholders, acting as educational human resources, by analyzing the capabilities, potential, weaknesses, and risks of existing environmental resources. Consequently, this research not only enriches theoretical knowledge but also provides guidance that needs to be considered in the quality development of an educational institution.